Activation and Impregnation of Chars — Nutshells and Pinewood Sawdust - Maria C.M. Alvim-Ferraz; Carla M.T.B. Gaspar (Adsorption Science & Technology)
The utilization of activated carbons as catalyst supports for the treatment of gaseous effluents contaminated with volatile organic compounds allows advantage to be taken both of the adsorption of the pollutant on the well-developed porous texture of activated carbons and the possibility of an efficient catalytic conversion. The step of catalyst impregnation should be optimized to obtain a catalyst dispersion compatible with good conversions at sufficiently low temperatures. Textural evolution when impregnation is performed either on the raw material or after activation of the latter has already been well studied. The work described in this paper was directed towards an analysis of the textural evolution of impregnated active carbons when the impregnation step was performed between carbonization and activation. To date, such knowledge is quite scarce. To allow comparison, impregnation with CoO, Co 3 O 4 or CrO 3 was carried out both after activation and after carbonization of nutshells and pinewood sawdust. For both raw materials, impregnation after activation involved deposition of the impregnated oxides on the internal surface of the materials thereby blocking part of the initial micro- and meso-porous textures. When impregnation was conducted after carbonization, metal species acted as catalysts during the subsequent activation step (Co 3 O 4 being the most efficient and CrO 3 the least efficient) and allowed the better development of the porous texture. In nutshell carbons, the metal species remained dispersed in micropores with a smaller volume but a larger size and in the mesoporous texture with a larger volume. Sawdust carbons retained a microporous texture with narrow pores in which the deposition of catalysts did not occur.